Expected profitability, independence, and risk assessment of small farmers in the wave of GM crop collectivization——evidence from Xinjiang and Guangdong - Yu Pang; Helin Zou; Chunchun Jia; Chao Gu (GM Crops & Food)
As a longstanding and indispensable part of developing countries, small farmers face challenges brought by the dissemination of GM technology. Despite governments’ efforts to promote collective cultivation of GM crops through top-down policies aimed at enhancing small farmers’ production efficiency and market competitiveness, actual participation rates among small farmers in many developing countries remain low. This reflects a gap and mismatch between policy design and the actual needs of small farmers. Based on a survey and empirical analysis of 964 small farmers in Guangdong and Xinjiang, China, this study finds that small farmers’ acceptance of GM technology is influenced not only by expected profitability but also by factors such as their independence and risk assessment of the technology. The findings reveal that, first, small farmers’ expected profitability from GM technology and their perception of independent market adaptability positively influence their willingness to participate in collective GM crop farming. Independent market adaptability acts as a partial mediator in this relationship and is moderated by small farmers’ risk assessments of GM technology. Variables such as gender, age, education level, and farming experience do not show significant effects. This study enriches the theoretical frameworks related to technology acceptance, innovation and diffusion, livelihood strategies, and collective transformation among small farmers in developing countries. It provides scientific evidence for policymakers to design more effective and aligned policies concerning GM crops.